Update on the 22q11.2 deletion syndrome and its relevance to schizophrenia. Issue 3 (May 2017) - Van, Lily; Boot, Erik; Bassett, Anne S.
Abstract : Purpose of review: Schizophrenia occurs in ∼25% of individuals with 22q11.2 deletion syndrome (22q11.2DS), the strongest known molecular genetic risk factor for schizophrenia. This review highlights recent literature in 22q11.2DS as it pertains to psychosis and schizophrenia. Recent findings: Advances in noninvasive prenatal testing allow for early detection of 22q11.2DS in utero, whereas premature birth has been shown to be a significant risk factor for development of psychotic illness in 22q11.2DS. Impairments in various domains of cognitive and social functioning, as well as neuroanatomical alterations, are comparable with those in other high-risk groups and may serve as early signs of psychosis in 22q11.2DS. Novel research on the pathogenesis of schizophrenia in 22q11.2DS using cellular and mouse models indicates changes in expression of genes within the 22q11.2 deletion region and elsewhere in the genome, implicating molecular pathways involved in schizophrenia and associated neurocognitive deficits. Increased risks of obesity and of Parkinson's disease in 22q11.2DS warrant consideration in antipsychotic management. Summary: Progress in characterizing and predicting psychotic illness in 22q11.2DS supports this identifiable subpopulation as a molecular model with important implications for understanding the pathogenesis of schizophrenia in the general population and for development of potential novel therapies.